(untitled) (Physical Education, Health and Social Sciences, 2026)
Musculoskeletal disorders (MSDs) constitute the leading occupational health burden in global agriculture, with prevalence ranging from 15.5% to 92% and a pooled estimate of 65.6%. This comprehensive review synthesizes evidence on the ergonomic assessment of traditional farm tools and the effectiveness of targeted redesign interventions to mitigate work-related MSDs among farm workers. Key risk factors prolonged awkward postures, repetitive motions, heavy lifting, and anthropometric mismatches drive excessive spinal compression (often exceeding the 770 lb NIOSH limit), rapid muscle fatigue (measured by sEMG shifts in mean frequency and RMS amplitude), and elevated physiological strain. Standardized observational tools (RULA for upper-limb tasks, REBA for whole-body dynamic work, and OWAS for field observations) are compared for their suitability in agricultural settings. Case studies of redesigned tools demonstrate substantial benefits: adjustable-handle hoes and chisel weeders reduce postural discomfort by 28–54%, spinal compression by 28%, and increase work capacity by 60–80%; ergonomic bucket carriers lower low-back disorder risk by 41–69%; and smaller harvest tubs cut pain by 20% with minimal productivity loss. Anthropometric data highlight the need for population-specific designs, particularly for smallholder and ethnic-minority farmers. Despite clear health and productivity gains, adoption barriers include high upfront costs, infrastructural limitations, low literacy, and cultural resistance. Policy support through ILO’s WIND participatory methodology, combined with emerging AI/machine-vision posture detection and frugal 3D-printed innovations, offers scalable solutions. Ergonomic tool redesign is therefore a high-impact, evidence-based strategy for reducing MSDs, enhancing worker well-being, and supporting sustainable agricultural productivity.